Biomechanical evaluation of the triangular support structure of the proximal femoral bionic nail compared to conventional long intramedullary nails for subtrochanteric fractures - Yang, Yanjiang; Wu, Dongwei; Cheng, Xiaodong; He, Wei; Chen, Wei; Zhang, Yingze; Zhang, Qi (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeThe aim of this study was to compare the biomechanical results of long proximal femoral bionic nail (PFBN) and three conventional intramedullary nails in the treatment of subtrochanteric fractures (STFs).MethodsUsing finite element analysis, we compared the therapeutic efficacy of four long intramedullary nails: the PFBN, reconstruction nail (RCN), InterTAN nail (ITN), and proximal femoral nail antirotation (PFNA) for the treatment of Seinsheimer type IIIA and type V STFs. The biomechanical stability of the implants was evaluated by calculating of von Mises stress (VMS), contact pressure and displacement for three loading scenarios.ResultsThe results showed that the PFBN group had the lowest VMS values under axial, bending and torsional loads. Under axial loading conditions, the VMS of PFBN was 480.04 MPa, followed by ITN (726.39 MPa), PFNA (730.48 MPa), and RCN (837.24 MPa) in the type V fracture groups. In the PFBN group, the contact pressure was 19.22 MPa and the tangential micromotion was 0.089 mm for the type IIIA group, 23.69 MPa and 0.08 mm for the type V group. Compared to the ITN, PFNA and RCN groups, the PFBN group exhibited the lowest contact pressure and tangential micromotion at the fracture sites.ConclusionThe superior biomechanical properties of the PFBN under axial, bending, and torsional loads not only reduced stress at the fracture site, but also improved structural stability.